Tra archivi e storia Scritti dedicati ad Alessandra Contini Bonacossi - Insabato, Elisabetta; Manno Tolu, Rosalia; Scattigno, Anna; Pellegrini, Ernestina (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2018)
The two volumes are dedicated to Alessandra Contini Bonacossi by the Association "Archivio per la memoria e la scrittura delle donne", which bears her name since 2007. They include a biographical profile, enriched by the list of her numerous publications, followed by thirty-two essays written by scholars who shared with her ideals and cultural interests of research and study and writings of her family members who make up the "family album". The collection, in addition to the variety of issues addressed in a wide chronological span - with essays ranging from the Middle Ages to the contemporary age - mainly focuses on the historiographical and interpretative reflection on documentary, iconographic, literary sources and themes such as Medici diplomacy, the Lorraine age, and gender history, to which Alessandra made important contributions with her studies.